Placing Human Agency in the AI-powered Media Localisation Industry - Orrego-Carmona, David (Journal of Audiovisual Translation, 2024)
The media localisation industry, as audiovisual translation (AVT) is commonly known, has undergone radical changes with the accelerated deployment of AI-powered solutions transforming production processes. This article examines how different stakeholders navigate this changing landscape: an industry promoting automation to meet growing demands, translators concerned about working conditions and professional sustainability, academia developing future professionals while researching technological impact, and audiences whose evolving expectations shape industry practices. Drawing on stakeholder theory, the analysis reveals how the sustainability of AVT requires balancing technological efficiency with human expertise. While AI tools promise faster turnaround times and reduced costs, their implementation must ensure long-term professional viability and translation quality. The article argues that successful integration of AI depends on creating value for all stakeholders through collaborative approaches that recognise translators’ agency and expertise. This requires conceptualising AI not merely as a cost-reduction tool but as part of a broader ecosystem where human expertise and technological capabilities complement each other to serve diverse global audiences. Lay summary Audiovisual translation is undergoing drastic changes due to the consolidation of an AI-powered media localisation industry. Escalating demands for faster content delivery, simultaneous releases in multiple languages, and changing production dynamics have been bolstered by an accelerated deployment of machine translation (MT) and AI technologies. This article assesses the impact of technology on media localisation by revising the perspectives of key stakeholders: industry representatives, professional translators, and academia. The review allows us to analyse the motivations and priorities of these stakeholders and, most importantly, the rationale guiding their positions. While the industry has embraced AI as an efficient response to the accelerated growth of media production and a solution to a declared shortage of professionals, professional associations have responded with strong warnings against post-editing and AI in media localisation. The magnitude and speed of recent changes have prompted primarily negative or cautious reactions from professionals. For them, the real issue lies in the deteriorating working conditions resulting from automated processes that ultimately lead to lower quality standards. As educators and researchers, we, as academics, are also in the midst of this evolving debate, grappling with the responsibility to quickly upskill ourselves to understand the nature and reach of the changes and to equip students with skills aligned with market demands; all this while instilling in them a critical awareness of these changes to ensure they can develop sustainable careers. After laying out the positions of these key stakeholders, the article proposes to encourage mutual recognition and awareness to foster understanding in an ever-evolving landscape. The potential of technology is evident, and its integration should not merely aim to replicate human work but should explore innovative ways to solve problems to address the complexities of creative translation processes. Ensuring the agency of human translators is recognised, the article constitutes a call to conceptualise processes that benefit from the expertise of human translators and successfully combine technological efficiency and human expertise to augment translation and expand the boundaries of media localisation.